Assessment of diastolic dysfunction: comparison of different cardiovascular magnetic resonance techniques. (20th July 2020) - Kermer, Josephine; Traber, Julius; Utz, Wolfgang; Hennig, Pierre; Menza, Marius; Jung, Bernd; Greiser, Andreas; Barckow, Philipp; von Knobelsdorff‐Brenkenhoff, Florian; Töpper, Agnieszka; Blaszczyk, Edyta; Schulz‐Menger, Jeanette
Abstract: Aims: Heart failure with preserved ejection fraction is still a diagnostic and therapeutic challenge, and accurate non‐invasive diagnosis of left ventricular (LV) diastolic dysfunction (DD) remains difficult. The current study aimed at identifying the most informative cardiovascular magnetic resonance (CMR) parameters for the assessment of LVDD. Methods and results: We prospectively included 50 patients and classified them into three groups: with DD (DD+, n  = 15), without (DD−, n  = 26), and uncertain (DD±, n  = 9). Diagnosis of DD was based on echocardiographic E/E′, invasive LV end‐diastolic pressure, and N‐terminal pro‐brain natriuretic peptide. CMR was performed at 1.5 T to assess LV and left atrial (LA) morphology, LV diastolic strain rate (SR) by tissue tracking and tagging, myocardial peak velocities by tissue phase mapping, and transmitral inflow profile using phase contrast techniques. Statistics were performed only on definitive DD+ and DD− (total number 41). DD+ showed enlarged LA with LA end‐diastolic volume/height performing best to identify DD+ with a cut‐off value of ≥0.52 mL/cm (sensitivity = 0.71, specificity = 0.84, and area under the receiver operating characteristic curve = 0.75). DD+ showed significantly reduced radial (inferolateral E peak: DD−: −14.5 ± 6.5%/s vs. DD+: −10.9 ± 5.9%/s, P  = 0.04; anterolateral A peak: DD−: −4.2 ± 1.6%/s vs. DD+: −3.1 ± 1.4%/s, P  = 0.04) and circumferential (inferolateral A peak: DD−: 3.8 ± 1.2%/s vs. DD+: 2.8 ± 0.8%/s, P  = 0.007; anterolateral A peak: DD−: 3.5 ± 1.2%/s vs. DD+: 2.5 ± 0.8%/s, P  = 0.048) SR in the basal lateral wall assessed by tissue tracking. In the same segments, DD+ showed lower peak myocardial velocity by tissue phase mapping (inferolateral radial peak: DD−: −3.6 ± 0.7 ms vs. DD+: −2.8 ± 1.0 ms, P  = 0.017; anterolateral longitudinal peak: DD−: −5.0 ± 1.8 ms vs. DD+: −3.4 ± 1.4 ms, P  = 0.006). Tagging revealed reduced global longitudinal SR in DD+ (DD−: 45.8 ± 12.0%/s vs. DD+: 34.8 ± 9.2%/s, P  = 0.022). Global circumferential and radial SR by tissue tracking and tagging, LV morphology, and transmitral flow did not differ between DD+ and DD−. Conclusions: Left atrial size and regional quantitative myocardial deformation applying CMR identified best patients with DD.